2001
DOI: 10.1109/4.953484
|View full text |Cite
|
Sign up to set email alerts
|

A low-light-level sensor for medical diagnostic applications

Abstract: Abstract-A low-level light sensor and preprocessor for a disposable medical probe is described. A 10-Hz 4-A/cm 2 input optical signal in the visible spectrum is assumed in chemoluminant diagnostic applications. A single-bit first-order sigma-delta modulator has been employed for analog-to-digital conversion, thanks to its robustness, simplicity, inherent linearity, and high signal-to-noise ratio. A current buffer has been used to replicate the weak signal with sufficient bandwidth. Tests have shown the feasibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 4 publications
(8 reference statements)
0
9
0
1
Order By: Relevance
“…We found that the detection limit of 1 nM of fluorophore could be reached when using the photosensor. Given that many schemes have been reported to increase the sensitivity and bandwidth of CMOS image sensors [35][36][37][38][39][40], improvement in sensitivity and imaging speed can be expected. Based on our targeted application for detection of AMC released from the QGSK-MCA substrate, the reaction kinetics involved favors detection within the second or sub-second temporal resolution range.…”
Section: Discussionmentioning
confidence: 98%
“…We found that the detection limit of 1 nM of fluorophore could be reached when using the photosensor. Given that many schemes have been reported to increase the sensitivity and bandwidth of CMOS image sensors [35][36][37][38][39][40], improvement in sensitivity and imaging speed can be expected. Based on our targeted application for detection of AMC released from the QGSK-MCA substrate, the reaction kinetics involved favors detection within the second or sub-second temporal resolution range.…”
Section: Discussionmentioning
confidence: 98%
“…(1-expf-t/rj] VGn(t)= Vdd·exp(-t/r) Having modeled the clock signal , each trans istor resistance amount versus time will be: According to (11) and (12), generated error rises versus time and reaches to its maximum amount at phase #2 which is defmed in Table I. Fig.…”
Section: C » Gate Falling Edge Transient Timementioning
confidence: 99%
“…The performance of these circuits has been studied with standard CMOS implementation [32][33][34]. Sigma-delta converters have been successfully integrated with CMOS image sensors [35][36][37].…”
Section: Analog-to-digital Conversionmentioning
confidence: 99%